Physiological characteristics of elite and sub-elite badminton players - Ooi, C. H.; Tan, A.; Ahmad, A.; Kwong, K. W.; Sompong, R.; Ghazali, K. A. M.; Liew, S. L.; Chai, W. J.; Thompson, M. W. (Journal of Sports Sciences, 2009)
The aims of this study were to establish the physical and physiological attributes of elite and sub-elite Malaysian male badminton players and to determine whether these attributes discriminate elite players from sub-elite players. Measurements and tests of basic anthropometry, explosive power, anaerobic recovery capacity, badminton-specific movement agility, maximum strength, and aerobic capacity were conducted on two occasions, separated by at least one day. The elite (n = 12) and sub-elite (n = 12) players' characteristics were, respectively: mean age 24.6 years (s = 3.7) and 20.5 years (s = 0.7); mass 73.2 kg (s = 7.6) and 62.7 kg (s = 4.2); stature 1.76 m (s = 0.07) and 1.71 m (s = 0.05); body fat 12.5% (s = 4.8) and 9.5% (s = 3.4); estimated VO2max 56.9 ml/kg·min (s = 3.7) and 59.5 ml/kg·min (s = 5.2). The elite players had greater maximum absolute strength in one-repetition maximum bench press (P = 0.015) compared with the sub-elite players. There were significant differences in instantaneous lower body power estimated from vertical jump height between the elite and sub-elite groups (P < 0.01). However, there was no significant difference between groups in shuttle run tests and on-court badminton-specific movement agility tests. Our results show that elite Malaysian male badminton players are taller, heavier, and stronger than their sub-elite counterparts. The test battery, however, did not allow us to discriminate between the elite and sub-elite players, suggesting that at the elite level tactical knowledge, technical skills, and psychological readiness could be of greater importance.